the اسلامی اخلاقی اقدارکے مغرب پر اثر ات کا تجزیاتی مطالعہ : An analytical study of the influence of Islamic moral values on the West - Muhammad Abu Bakar; Shahid iqbal (AL-IDRAK JOURNAL, 2023)
Islamic values recorded the most impressions on the collective and individual level in the human universe. The influence of Islamic scientific and moral values on Western civilization is significant and clear. There is no aspect of European civilization and moral values that is not definitely influenced by Islamic civilization. It is an indisputable historical fact that darkness covered Europe in the Middle Ages. When the rays of Islamic civilization fell on the dark civilization of Europe, the radiant light of Islamic moral values only freed their minds from myths. As a result, they were freed from the humiliating and tyrannical monarchy of the Church and moved towards freedom. The paper examines the impact of Islamic moral values on Western society.